Pelatihan Pembuatan Nata De Soya dari Limbah Cair Tahu di Kelurahan Indihiang, Kota Tasikmalaya - Mufti Ghaffar; Maerani; Rizka Fikrinnisa; Risa Nurul Saadah; Dika Pratama; Indri Susanti; Keiza Lingga Arieswara (Altifani Journal: International Journal of Community Engagement, 2024)
Indihiang Village is one of the areas with the largest number of tofu maker in Tasikmalaya City. However, the number of tofu maker is directly proportional to the amount of waste produced. Tofu liquid waste that is not used properly then becomes an environmental problem because it causes an unpleasant odor. Apart from that, tofu liquid waste that is thrown into rivers can disrupt the aquatic ecosystem. The aim of this community service activity (PkM) is to increase public knowledge regarding the use of tofu waste and its processing into Nata De Soya in Indihiang Village, Tasikmalaya City. This training activity was carried out on September 19 2024 at the hall of the Indihiang Village Office, Tasikmalaya. Participants in this training activity were the Indihiang Village Family Welfare Empowerment Team. The PkM stages include problem identification, PkM location survey and coordination with the Indihiang Village as well as a demonstration on making Nata De Soya. The success of PkM activities was marked by increasing public knowledge regarding the use of tofu liquid waste to make Nata De Soya, which was marked by an increase in the score on the post test by 19 points. After the activities were carried out, the PKK team gained knowledge and skills in managing tofu liquid waste into nata de soya